2019
DOI: 10.1016/j.jemermed.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Physicians’ Perception of Barriers and Facilitators for Adopting an Opioid Prescribing Guideline in Ohio: A Qualitative Interview Study

Abstract: Background Ohio has the fifth highest rate of prescription opioid overdose deaths in the United States. One strategy implemented to address this concern is a state-wide opioid prescribing guideline in the emergency department (ED). Objective Our aim was to explore emergency physicians’ perceptions on barriers and strategies for the Ohio ED opioid prescribing guideline. Methods Semi-structured interviews with emergency physicians in Ohio were conducted from October to December 2016. Emergency physicians wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This is important, since lower patient satisfaction scores from decreased unnecessary opiate prescription can be a barrier for physicians in implementing these reduced prescribing practices. 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important, since lower patient satisfaction scores from decreased unnecessary opiate prescription can be a barrier for physicians in implementing these reduced prescribing practices. 23…”
Section: Discussionmentioning
confidence: 99%
“…This is important, since lower patient satisfaction scores from decreased unnecessary opiate prescription can be a barrier for physicians in implementing these reduced prescribing practices. 23 Another reason for the historical routine opiate prescription is that surgeons inherently would rather err on the side of reduced patient suffering. These practices can only be altered by good science.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis was conducted during ongoing recruitment to allow the evaluation of sample size requirements in relation to thematic saturation (Malterud et al., 2016). The required sample size was projected to be approximately 30 interviews based on existing literature (Breen et al., 2007; Penm et al., 2019). Recruitment continued until new themes relevant to the objective of this study were no longer observed.…”
Section: Methodsmentioning
confidence: 99%
“…The survey received a 92% response rate, and the majority of the respondents (71%) believed that the guidelines did help to reduce inappropriate opioid prescribing [ 9 ]. In a related qualitative study consisting of interviews with emergency physicians in Ohio, concerns were expressed with the guidelines, including a perceived lack of organizational responsibility on behalf of hospitals to address inappropriate opioid prescribing [ 10 ]. These physicians also commented on prescribers’ unconscious bias toward patients at high risk of opioid overdose and prescribers’ lack of education and awareness about take-home naloxone [ 11 ].…”
Section: Overview Of the Opioid Crisis In The United States And Inmentioning
confidence: 99%